Leadership for democratic development in Tanzania: the perspective of Mwalimu Julius K. Nyerere during the first decade of independence - Haussler, Peter (Department of Social Development, 2023)
This study analyses the perspectives about 'good leadership' as spelt out by an outstanding African leader, Julius Karnbarage Nyerere, who ruled Tanzania from independence in 1962 until 1985, and influenced African history until his death in 1999. This research reveals an exciting and interesting time in politics and social development in Africa, and puts questions forward in order to unveil Nyerere's perspectives on leadership. The particular period investigated is the decade of the 1960s, the critical time of independence and nation building. The study is composed of two parts, the understanding of the context of Tanzania's development, and the hermeneutical analysis of Nyerere's perspectives. To understand Nyerere in his context, I randomly selected seven authentic speeches and a handpicked one. I used content analysis (manifest and latent coding) and hermeneutics as my methodological approaches. Key-concepts explored in the study were Democracy, Development, Unity and Peace, and Leadership. The underlying assumption of this study is that 'good leadership' is needed to promote participation, democracy and socio~economic development, creating national stability. The research proves this assumption right. The qualitative character of the research does not allow for generalisation of the results, which is limited by the small sample of speeches. However, recent challenges of economic globalisation and its impact on the 'poor' countries remind us of the social and political responsibility of leaders. Understanding the importance of good leadership for development is one of Nyerere's legacies. Political leadership has to be learnt. Core to the research was a "dialogue' between Nyerere, in his historical, political and personal context, and I, in mine. Hans-Georg Gadamer, a prominent henneneuticaJ philosopher. taught me how to understand first, in order to interpret and then to influence social reality. I have developed a methodological technique, the 'triple•jump', to understand and to interpret the text and to approach the 'truth'. The central research question, "what in Nyerere's perspective is a good lead.er for democratic development?" could be answered through the study: a leader has to be ethical, reliable, knowledgeable, decisive, accountable, humble, hard working and socially responsible. Nyerere's perspectives on good leadership also serve as guidance to contemporary political leaders, who are committed to democratic development. It is hoped that the results of this study will enrich the Youth Leadership Training Programme (YL TP) in Tanzania and other leadership training programmes elsewhere in Africa.